Case Report: Haploidentical Bone Marrow Transplantation in Two Brothers With Wiskott–Aldrich Syndrome Using Their Father as the Donor - Smith, Jasmine; Alfonso, Jessica Hass; Reddivalla, Naresh; Angulo, Pablo; Katsanis, Emmanuel (Frontiers in Pediatrics, 2021)
Wiskott-Aldrich Syndrome (WAS) is an X-linked genetic disorder with a variable phenotypic expression which includes thrombocytopenia, eczema, and immunodeficiency. Some patients may also exhibit autoimmune manifestations. Patients with WAS are at increased risk of developing malignancies such as lymphoma. Allogeneic hematopoietic cell transplantation remains the only curative treatment. Haploidentical bone marrow transplantation (haplo-BMT) with post-transplant cyclophosphamide (PT-CY) has more recently been applied in WAS. Here, we report two brothers who underwent successful T-cell replete haplo-BMT with PT-CY at ages nine months and four years using their father as the donor. Our myeloablative regimen was well tolerated with minimal organ toxicity and no acute or chronic graft versus host disease (GvHD). Haplo-BMT may be considered as a safe and effective option for patients with WAS who do not have available human leukocyte antigen (HLA) matched donors.